A statistical study of the response of the dayside equatorial F2 layer to the main phase of intense geomagnetic storms as an indicator of penetration electric field - Balan, N.; Yamamoto, M.; Sreeja, V.; Batista, I.S.; Lynn, K.J.W.; Abdu, M.A.; Ravindran, S.; Kikuchi, T.; Otsuka, Y.; Shokawa, K.; Alex, S. (My University, 2011)
The response of the dayside equatorial F2 layer to the main phases of the 22 intense geomagnetic storms (Dst < −150 nT) in 1998–2008 is investigated using the digital ionosonde data from the equatorial stations in Brazilian, Indian, and Australian longitudes together with equatorial electrojet strength and IMF Bz; the storms include 15 superstorms (Dst < −200 nT). The observations show that there is a period during all MPs when the F2 layer peak rises (and falls) rapidly with large peak electron density (Nmax) reduction, the rise velocity strongly correlates with the intensity (Dst) of the storms, and the duration of the Nmax reduction corresponds to that of strong eastward electrojet when IMF Bz remains highly negative. The observations indicate the occurrence of strong eastward prompt penetration electric fields (PPEF) during the rapid F2 layer response. The PPEF drives the F2 layer peak rapidly upward, which reduces Nmax due to vertical expansion and diffusion. The results therefore suggest that the rapid F2 layer response (rapid rise (and fall) of peak height (hmax) with large Nmax reduction) observed by ionosondes can be used to detect the occurrence of the daytime eastward PPEF during intense geomagnetic storms irrespective of season and level of solar activity. The data also show two rare events of strong daytime westward electric fields due to disturbance dynamo and/or prompt penetration. The results are important when radars are not available to monitor the occurrence of the PPEF.
Keywords: Dayside equatorial F2 layer; Geomagnetic storms; Prompt penetration electric fields; PPEF